Thriving Beyond Resilience Despite Stress: A Psychometric Evaluation of the Newly Developed Teacher Stress Scale and Teacher Thriving Scale - Chen, Jennifer J.; Li, Zijia; Rodrigues, Wilson; Kaufman, Samantha (Frontiers in Psychology, 2022)
Building on theoretical and empirical insights and applying the thriving theory as the conceptual framework, the authors developed two teacher-specific scales, namely the Teacher Stress Scale (TSS) and the Teacher Thriving Scale (TTS). The goal of this investigation was to evaluate the psychometric properties of these two scales. Data were collected through an online questionnaire administered to a national sample of 122 early childhood teachers (ages 22-72 years, M = 41.01) teaching in preschool through 3rd grade in 26 states of the United States during the 2020-2021 school year amidst COVID-19. This study revealed some important psychometric results. First, with respect to their internal structures, both the TSS and the TTS appeared to be best represented as multifactorial. As such, the TSS comprised two constructs: (1) Inadequate School-based Support, and (2) Teaching-related Demands; and the TTS encompassed three constructs: (1) Adaptability and Flexibility, (2) Personal Strengths and Professional Growth, and (3) Positive Mindset. Second, the negative correlation between the TSS and the TTS provided discriminant evidence for construct validity, while the positive correlations between TTS and other conceptually cognate constructs (Stress Resilience, Resilience Coping, Coping Efficacy, Teaching Job Satisfaction, Emotional Support, and Gratitude) demonstrated convergent evidence for construct validity. Third, both the overall TSS and the overall TTS as well as their subscales exhibited good internal consistency reliability. Fourth, both the overall TSS and the overall TTS also demonstrated test-retest-reliability.